Cooperative learning and achievement in english language acquisition in a literature class in a secondary school - Tok, Hoon Seng (2006)
Cooperative learning is a teaching arrangement that refers to small, heterogeneous groups of students working together to reach a common goal. Its effectiveness had been documented through numerous research studies. However, very few published materials have been done on the relationship between the use of cooperative learning as a teaching method to increase students' achievement in learning English literature in secondary school. Therefore, the purpose of this study was to discover the relationship between cooperative learning and achievement in English language acquisition in a literature class in a secondary school. It is hoped that this study could help overcome the problems of students who have low English language proficiency in secondary schools. This study was conducted in a rural secondary school. A total of 59 respondents from Form 4 classes have participated. The experimental group received teaching method using cooperative learning strategies, while the control group received traditional lecture method. Qualitative and quantitative data were gathered in this study using four types of instruments: pre-test and post-test questions, questionnaires, classroom observations and interviews. Data analysis was done using SPSS version 9.0 program. It was found that all respondents showed a low and moderate performance in English Literature before the treatment. However, after the treatment, respondents from the experimental group showed a significant improvement. Those from the control group did not show similar improvement. Thus, the use of cooperative learning played an important role in acquiring English language in an English literature class. Furthermore, the qualitative data showed that cooperative learning could enhance students’ social development as well as interest in the learning of English literature. In conclusion, this study had proven that cooperative learning enhances students’ achievement in learning English literature.